Gadai Sawah dengan Sistem Tradisi Tanah Digarap Rahin Perspektif 'Urf - Toyyibatul Hasanah; Moh. Irfan (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2022)
This research was conducted with the aim of finding out how the practice of mortgage rice fields with the traditional system of tilled land is rahin and an analysis of Islamic law on the practice of mortgaging rice fields carried out by the people of Lajing village, Arosbaya sub-district, Bangkalan district. This research is an empirical research that is descriptive in nature. The results of the study showed that the practice of mortgage rice fields in Lajing village, Arosbaya sub-district, Bangkalan district, namely paddy field mortgage with the traditional system of land being worked on by the rahin and no time limit for the pawn contract's expiration. Then murtahin will get the harvest from the field until the rahin can pay off his debt. The practice of mortgage rice fields with the tradition system of land tilled rahin is a valid tradition (urf al-Sahihah) because this tradition does not conflict with the rules of Islamic law.